Profits and Rates of Return in OECD Countries - Chan-Lee, James H.. (OECD Economics Department Working Papers, 1985)
There is widespread concern, particularly in Europe, about the possibility of a secular decline in profits and rates of return. The purpose of this study is to assess whether there has been a decline and to quantify it as far as possible, taking measurement problems into account. It also considers summarily the significance of observed trends and the reasons for them. Profits are generally seen as an essential feature of market economies. When they are low, it is feared that enterprise and innovation will falter and the rate of investment decline, leading to sluggish growth in output and capacity. Low growth may also lead to low profits. The precise links between profits and economic performance are, however, theoretically complicated and difficult to establish empirically. This is because both economic and accounting definitions of profit cover heterogeneous phenomena and are calculated as a residual. Conceptual and measurement issues are important in assessing the evolution of ...